2017
DOI: 10.1111/jfd.12608
|View full text |Cite
|
Sign up to set email alerts
|

Salmon gill poxvirus, a recently characterized infectious agent of multifactorial gill disease in freshwater‐ and seawater‐reared Atlantic salmon

Abstract: Gill diseases cause considerable losses in Norwegian salmon farming. In 2015, we characterized salmon gill poxvirus (SGPV) and associated gill disease. Using newly developed diagnostic tools, we show here that SGPV infection is more widely distributed than previously assumed. We present seven cases of complex gill disease in Atlantic salmon farmed in seawater and freshwater from different parts of Norway. Apoptosis, the hallmark of acute SGPV infection, was not easily observed in these cases, and qPCR analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 19 publications
(55 reference statements)
8
85
0
Order By: Relevance
“…Other aspects correspond very well with previous reports (Gjessing et al., , ) in salmon including, peracute disease course afflicting almost all fish in a tank synchronously, disease spread from tank to tank, gill histopathology including apoptosis of gill epithelial cells and in some cases signs of extensive blood cell breakdown in hematopoietic organs suffering SGPVD. However, the smallest fish are challenging to examine by histology as the organs may be entirely or partly missing in the sections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other aspects correspond very well with previous reports (Gjessing et al., , ) in salmon including, peracute disease course afflicting almost all fish in a tank synchronously, disease spread from tank to tank, gill histopathology including apoptosis of gill epithelial cells and in some cases signs of extensive blood cell breakdown in hematopoietic organs suffering SGPVD. However, the smallest fish are challenging to examine by histology as the organs may be entirely or partly missing in the sections.…”
Section: Discussionsupporting
confidence: 92%
“…As apoptosis could be difficult to observe in such cases, the SGPV qPCR is recommended. The SGPVD problems appeared very widespread as the cases represented both seawater farms and freshwater farms with both recirculation aquaculture systems (RAS) and flow‐through systems (Gjessing, Thoen, Tengs, Skotheim, & Dale, ). In addition, SGPV was reported as prevalent in gills with lesions characteristic for SGPVD in wild salmon broodfish (Garseth, Gjessing, Moldal, & Gjevre, ).…”
Section: Introductionmentioning
confidence: 99%
“…In farmed salmon, SGPV has been recorded at all stages of the production cycle, including hatcheries that do not use sea water in their production (Gjessing et al., ). For the salmon farming industry, the role of horizontal transmission from wild reservoirs in the freshwater source and the role of vertical transmission from broodfish are important questions to resolve.…”
Section: Discussionmentioning
confidence: 99%
“…Low amount of SGPV may be detected in fish without signs of disease or clear pathological changes. However, high amount of the virus is often associated with high, acute mortality during the freshwater phase, but can also cause disease and mortality after sea transfer (Gjessing et al., ). The widespread distribution and impact of SGPV in farmed fish has caused concern regarding its occurrence and impact on wild fish.…”
Section: Introductionmentioning
confidence: 99%
“…Le wisch et al (2015) suggested that the reduced immune status of the carp accounts for the severity of secondary infections and may explain the chronic nature of the disease during naturally occurring outbreaks. The gill damage induced by salmon gill poxvirus has been suggested to impair innate immunity and allow infections by secondary invaders (Gjessing et al 2017). Immunosuppression also plays a role in the pathogenesis of mammalian poxvirus infection (Stra yer 2012).…”
Section: Clinical Signs Of Diseasementioning
confidence: 99%